Incidence of thromboembolic complications in hospitalized COVID-19 patients in a medical ward in Japan: A single-center retrospective and prospective observational study. Issue 33 (19th August 2022) - Komagamine, Junpei; Yabuki, Taku
Abstract : Background: A high incidence of thromboembolic complications is one of the hallmarks of COVID-19. However, there may be a difference in the incidence of thromboembolic complications between Asian and Western people. In addition, few prospective studies have been conducted to determine the incidence of thromboembolic complications in hospitalized COVID-19 patients in medical wards in Japan. Methods: A single-center retrospective and prospective cohort study was conducted to determine the incidence of thromboembolic complications in symptomatic COVID-19 patients in a medical ward in a Japanese hospital. All 1116 consecutive COVID-19 patients who were admitted to our hospital from November 1, 2020, to October 26, 2021, were included. The primary outcome was any thromboembolic complications, which included venous thromboembolism, myocardial infarction, ischemic stroke, and other arterial embolisms. Results: The median patient age was 50 (IQR, 37–61), 402 (36.0%) were women, 1005 (90.1%) were Japanese, the median body mass index was 24.1 (IQR, 21.6–27.2), and 43 (3.9%) had Padua scores of at least 4 points at admission. Regarding the severity of COVID-19, 543 (48.7%), 315 (28.2%), 204 (18.3%), and 54 (4.8%) patients had mild, moderate, severe, and critical COVID-19, respectively. Nine patients (0.8%) died, and 47 patients (4.2%) were transferred to other hospitals for intensive care. The primary outcome occurred in only 5 patients (0.5%; 95% CI, 0.1–0.8) and consisted of 3 ischemic strokes, 2 limb ischemia events, and one asymptomatic pulmonary embolism. Even in the 204 patients with severe COVID-19, the prevalence of thromboembolic complications was only 2.5% (95% CI, 0.3–4.6). Conclusion: Thromboembolic complications of COVID-19 are rare even in severe cases in a medical ward in a Japanese hospital. Further studies are needed to identify severe COVID-19 patients with a higher risk for thromboembolic complications in Japan.